2016
DOI: 10.1002/jemt.22798
|View full text |Cite
|
Sign up to set email alerts
|

Tissue integrity, costs and time associated with different agents for histological bone preparation

Abstract: The selection of an appropriate demineralizing solution in pathology laboratories depends on several factors such as the preservation of cellularity, urgency of diagnostic and financial costs. The aim of this study was to test different decalcification bone procedures in order to establish the best value of these in formalin-fixed and paraffin-embedded samples. Femurs were removed from 13 adult male Wistar rats to obtain 130 bone disks randomly divided into five groups that were demineralized in different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
(18 reference statements)
3
10
0
Order By: Relevance
“…Importantly, demineralization of the surface did not result in any detectable molecular changes to the osseous surface other than the depletion of mineral. With respect to EDTA, this observation is in line with reported data showing preservation of the organic portion of the matrix post EDTA treatment [21]. We believe that the molecular characterization of osseous surface models provides an important benchmark in the future development of studies addressing the interaction of bone cells with osseous surfaces.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, demineralization of the surface did not result in any detectable molecular changes to the osseous surface other than the depletion of mineral. With respect to EDTA, this observation is in line with reported data showing preservation of the organic portion of the matrix post EDTA treatment [21]. We believe that the molecular characterization of osseous surface models provides an important benchmark in the future development of studies addressing the interaction of bone cells with osseous surfaces.…”
Section: Discussionsupporting
confidence: 88%
“…47,48 Some studies have reported acceptable results obtained with hydrochloric or nitric acid. 10,22,26,44 In contrast, the findings from this study were in agreement with Neves et al, who found specific positive staining despite poor tissue morphology, and concluded that hydrochloric acid should be avoided for bone decalcification if preservation of bone matrix and antigenicity is desired. 49 Moreover, Athanasou et al reported that sufficient fixation and controlled decalcification in hydrochloric and nitric acids had no negative effects on diagnostic markers, such as vWF or prostate-specific antigen.…”
Section: Discussionsupporting
confidence: 92%
“…When decalcified in EDTA, formic acid, or nitric acid, the cartilage showed weaker staining at 37C. These findings complement the results of several other studies, confirming that both fixation and decalcification methods have been associated with proteoglycan and glycosaminoglycan depletion 4,26,27,32 reducing the staining intensity of Safranin O, which is directly proportional to the proteoglycan content in normal cartilage. 37 Optimal fixation and decalcification conditions for cartilage-containing specimens should always be decided in a pilot study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…She shared her vast experience in her paper and gave detailed insights into the problems and troubleshooting methods she had developed over the years. “Morse’s solution” or “Anna Morse solution” is still widely used in hard tissue histology and performs well in modern histology laboratories as a reliable reagent for rapid and effective tissue decalcification (Abrantes et al 2017). Morse moved to the Harvard School of Dental Medicine, where she continued to develop histological methods, focusing on the visualization of enzyme activity in hard tissue specimens.…”
Section: Star Papersmentioning
confidence: 99%